SWOT ANALYSIS FOR DETERMINING COMPETITIVE STRATEGY IN THE TEA PLANTATION UNIT MALABAR - Pardian, Pandi; Heryanto, Mahra Arari; Chabibah, Chabibah; Jayusman, Hera Kusmiati; Larasati, Farah; Madasanasa, Amienda Cahya; Fadhilah, Adistia (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Malabar tea plantation is one of the first plantations in Pangalengan managed by PT Perkebunan Nusantara VIII. Malabar tea products have been known in various countries. However, tea production activities fluctuate yearly, and competition with companies in the same field is getting tighter. Therefore, the right strategy is needed to be more competitive. This study aims to create a competitive advantage strategy for Malabar Tea Plantation as a tea producer in the Malabar production unit. This study uses SWOT and descriptive analysis. The study results showed that the main strength is the complete Malabar Factory product certification, with a score of 1.30, and the main weakness is the lack of maintenance in the field, with a score of 1.18. The opportunity is the expansion of tea marketing and the improvement of the downstream industry, with a score of 1.37, and the threat is the EGVC (Empowerment of Plantation and Village Communities) partners, who are less cooperative, with a score of 1.13. Based on this, the Malabar plantation unit is in quadrant 1, which means it is in a growth position, so the strategy implemented is an aggressive strategy, including market penetration, seeking new potential customers, and maintaining good relationships with old customers.